Developing An English Supplementary Writing Materials-Based On The Contextual Teaching And Learning - Ahmad Kanzul Ilmi; Salamun; Muhammad A'inul Haq (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
The study was educational Research and Development (R & D). The procedure of the study was conducting need analysis, material development, expert validation, revision I, try out, revision II, and the final steps are the final product. The instruments of the study were questionnaires and interview guidelines. Respondents are the teacher of the English lesson and students of tenth-grade senior high school Islam Parlaungan Waru. The result shows that the students needed interesting additional writing materials. The product of this supplementary writing material is entitled Write for Future. The study guide book is completed with a warming up, discussion, and practice. The additional English writing materials book consists of four chapters. Each chapter has a topic that is different from one another. Those are 'You Also Need To See A Doctor for the first topic,